Pengaruh Media Sosial dan Komunitas Daring dalam Literasi Keuangan Syariah Generasi Z - kumaidi, kumaidi; Abbas, Darul Qotni (Economic Reviews Journal, 2025)
This research examines the role of social media and online communities in building sharia financial literacy among Generation Z in Indonesia through a systematic literature review following PRISMA 2020 guidelines. A review of academic research, official reports, and related publications (2017–2025) identified three main interacting elements: (1) social media as an educational gateway—especially visual platforms like Instagram and TikTok; (2) online communities (Telegram groups, WhatsApp, forums) that strengthen collective learning through discussions and peer-to-peer learning; and (3) critical digital literacy which acts as a filter for the validity of sharia content. The synthesized findings indicate that sharia financial literacy serves as a primary mediator between digital exposure and changes in financial behavior, such as an increased tendency to save and invest in sharia instruments and a reduction in consumptive behavior triggered by viral content. However, the effectiveness of content depends on credibility, narrative quality, and user engagement; entertainment-oriented platforms like TikTok risk encouraging impulsiveness without a foundation of literacy. The study also shows that religiosity acts as a strong motivator in the adoption of sharia products. The article formulates a synergistic model (social media + online communities + digital literacy) as an adaptive framework for Islamic financial education. It also highlights the challenges of information verification and the need for a contextual and evidence-based content strategy. Practical recommendations are presented for financial education stakeholders, regulators, and sharia industry players.